Kinetics of the reaction of alkylamines with 7,7,8,8-tetracyanoquinodimethane (TCNQ) in organic solvents - El Seoud, Omar A.; Ribeiro, Francisco P.; Martins, Abilio [UNESP]; Brotero, Paula P. (My University, 1985)
The following sequence of substitution reactions was studied spectrophotometrically in organic solvents: RNH2 + TCNQ →-HCN 7-substituted TCNQ →-HCN +RNH2 7.7-disubstituted TCNQ where R = butyl, octyl, dodecyl, and hexadecyl. The production of 7-(alkylamino)-7,7,8-tricyanoquinodimethanes proceeds via the formation of the anion radical of TCNQ (TCNQ-·) whose rate of appearance was found to be a function of the chain length of R, reaching a maximum for octylamine. The formation of TCNQ-· was sensitive to the solvent polarity and electron-donor power and was associated with a small enthalpy and a highly negative entropy of activation. Above a certain [C8H17NH2] the rate of disappearance of TCNQ-· was independent of the amine concentration, and the reaction had a much higher enthalpy and entropy of activation. The occurrence of tautomerism precluded an investigation of the conversion of 7-(octylamino)-7,8,8-tricyanoquinodimethane into 7,7-bis(octylamino)-8,8-dicyanoquinodimethane. A study of the reaction of octylamine with 7-morpholino-7,8,8-tricyanoquinodimethane (which does not exist in tautomeric forms) showed that the second substitution step proceeds with the same mechanism as the first one. The only difference between the two compounds (TCNQ and its monosubstituted morpholino derivative) is one of reactivity. © 1985 American Chemical Society.